Secondary hypertension and hirsutism as a clinical manifestation of tumor duplicity - Frysak, Zdenek; Karasek, David; Hartmann, Igor; Kucerova, Ladislava (Biomedical papers, 2015)
Background: The differential diagnosis of the pathogenetic causes of hirsutism in combination with hypertension is a challenge for clinicians.Methods and Results: This case report demonstrates a patient suffering from two hormonally active tumors - an adrenal adenoma with primary aldosteronism and a Leydig cell ovarian tumor with hyperandrogenism. The task of the authors was easier due to the perimenopausal age of the proband. Adrenal selective venous sampling was very helpful in the diagnosis of these active endocrine tumors. Both were resolved by a single laparoscopic surgery.Conclusion: The combination of the two described tumors is a unique clinical finding. The resolution using laparoscopy in a single procedure provided an elegant and efficient therapeutic approach.
Keywords: hirsutism; secondary hypertension; aldosterone-producing adenoma; Sertoli-Leydig cell tumor